Pengaruh Praktek Kerja Lapangan, Unit Produksi Dan Dukungan Keluarga Terhadap Kesiapan Kerja Siswa Di SMK Negeri 2 Bukittinggi - Metra Linda Harnety; Almasdi Almasdi (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2022)
Vocational High School (SMK) is a form of formal education unit that aims to prepare prospective middle-level workers to enter the world of work. Factors that affect student work readiness can be seen from internal and external factors. This study aims to reveal the effect of on job training, production units and family support on student work readiness at SMK Negeri 2 Bukittinggi. The research subjects were students of SMK Negeri 2 Bukittinggi. A sample of 130 students was determined using the proportionate stratified random sampling technique. This type of research is quantitative research. Data collection techniques using a questionnaire with a Likert scale model of 5 alternative answers. Data analysis was performed using SEM (Structural Equation Modeling) analysis which was operated based on Partial Least Square (PLS) with three independent variables and one dependent variable. This study results that on job training and production units have a positive and significant effect on the readiness of students at SMK Negeri 2 Bukittinggi, while family support has a negative and insignificant effect on job readiness of students at SMK Negeri 2 Bukittinggi.